Identification of ectoparasites and endoparasites on fruit bats (Cynopterus brachyotis) in Ketapang Timur Village, Ketapang Sub-District, Sampang District - Mohamad Safri Sauqi; Tjuk Imam Restiadi; Setiawan Koesdarto; Poedji Hastutiek; Boedi Setiawan; Agus Wijaya (Journal of Parasite Science (JoPS), 2021)
This study aims to determine the ectoparasites and endoparasites that infest fruit bats (Cynopterus brachyotis) in Ketapang Timur, Ketapang District, Sampang Regency. The samples in this study were blood, feces and ectoparasites from 50 fruit bats taken in Ketapang District, Sampang Regency. Blood samples were examined using a blood smear method with Giemsa staining, while stool samples were examined using three methods, namely native, sucrose floating, and acid-fast modification. Blood examination was checked using a microscope with 1000x magnification and stool examination at 400x magnification. The sample is considered positive if under microscope observation found parasites that match the characteristics of the protozoa sourced from scientific references. The results of the study of 50 fruit bats examined found five positives for digestive protozoa and ectoparasites, the infection was single, with details of one tail being infected with Eimeria sp. and one tail was infected byÂ Leptocyclopodia ferrarii, while blood protozoa were not found. This study concludes that the type of protozoa found in the digestive tract is Eimeria sp. (14%) and ectoparasite Leptocyclopodia ferrarii. (2%). The total percentage obtained was 16% positive for a single infection of protozoa and ectoparasites from 50 fruit bats. Suggestions that can be put forward are to conduct further research using PCR and sequencing to obtain more specific and accurate identification results, for subspecies or strains.